2019
DOI: 10.1111/cxo.12809
|View full text |Cite
|
Sign up to set email alerts
|

Focal cortical cataract due to caterpillar hair migration

Abstract: Figure 2. Two years after exposure, the caterpillar setae appear to have migrated in the eye. One of them was stuck in the anterior capsule and had produced a small anterior subcapsular opacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The setae can subsequently be propelled into intraocular structures, from the anterior chamber into the lens, vitreous humor, and retina. 4 A retrospective analysis published in 2010 by Sengupta et al 8 found that the only significant risk factor for intraocular penetration of caterpillar hair was the presence of deep intracorneal hair at diagnosis, and the removal of intracorneal hairs was only possible in 36% of cases. This illustrates that once setae or hairs have traveled intraocularly, it is exceedingly difficult to remove them and these cases require close interval follow-up to monitor for further serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…The setae can subsequently be propelled into intraocular structures, from the anterior chamber into the lens, vitreous humor, and retina. 4 A retrospective analysis published in 2010 by Sengupta et al 8 found that the only significant risk factor for intraocular penetration of caterpillar hair was the presence of deep intracorneal hair at diagnosis, and the removal of intracorneal hairs was only possible in 36% of cases. This illustrates that once setae or hairs have traveled intraocularly, it is exceedingly difficult to remove them and these cases require close interval follow-up to monitor for further serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Similarly, only a small number of intra-lenticular setae have been recorded. [ 8 12 ] Agarwal et al . [ 13 ] described a case where a young woman was found to have several caterpillar hairs in areas of her eye, including her AC, sclera, cornea, and pars plana.…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, setae can embed in the eye and cause an inflammatory reactionophthalmia nodosa-most commonly caused by caterpillars of the pine processionary moth (Thaumetopoea pityocampa) and characterized by immediate chemosis, which can progress to liquefactive necrosis and hypopyon, later developing into a granulomatous foreignbody response. 2,10 The process is thought to be the result of a combination of the thaumetopoein toxin in the setae and an IgE-mediated response to other proteins. 10 Due to their harpoon shape and forward-only motion, setae might migrate deeper, potentially even to the optic nerve.…”
Section: Spilosoma Glatignyi None Australiamentioning
confidence: 99%
“…2,10 The process is thought to be the result of a combination of the thaumetopoein toxin in the setae and an IgE-mediated response to other proteins. 10 Due to their harpoon shape and forward-only motion, setae might migrate deeper, potentially even to the optic nerve. 11 Because migration might take years and the barbed shape of setae does not always allow removal, some patients require lifetime monitoring with slit-lamp examination.…”
Section: Spilosoma Glatignyi None Australiamentioning
confidence: 99%
See 1 more Smart Citation